2018
DOI: 10.1155/2018/9084279
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on Behavior of a New Connector Used in Bamboo (Timber) Frame Structure under Cyclic Loading

Abstract: Connection is an important part of the bamboo and timber structure, and it directly influences the overall structural performance and safety. Based on a comprehensive analysis of the mechanical performance of several wood connections, a new connector for the bamboo (timber) frame joint was proposed in this paper. Three full-scale T-type joint specimens were designed to study the mechanical performance under cyclic loading. The thickness of the hollow steel column was different among three specimens. The specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results revealed that employment status was the only sociodemographic factor that had a significant effect on the aesthetic preference of the respondents. This finding is consistent with some previous studies that have found employment status to be a predictor of aesthetic preference [61,62]. This finding is interesting, as it suggests that employment status may be related to other factors, such as income, lifestyle, values, or exposure to design, that may affect the aesthetic judgment and preference of consumers [10,53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results revealed that employment status was the only sociodemographic factor that had a significant effect on the aesthetic preference of the respondents. This finding is consistent with some previous studies that have found employment status to be a predictor of aesthetic preference [61,62]. This finding is interesting, as it suggests that employment status may be related to other factors, such as income, lifestyle, values, or exposure to design, that may affect the aesthetic judgment and preference of consumers [10,53].…”
Section: Discussionsupporting
confidence: 91%
“…As highlighted by Yang et al [59], timber joints provide strength and stability to the overall building, evolving over time under the influence of regional traditions, material, and technological advancements, and the need for efficient construction methods [60]. Traditional timber joints, such as mortise and tenon joints, have a rich history in Asian countries, preserving the original beauty and aesthetics of timber without relying on steel fasteners [61]. However, advancements in fasteners and joint design have revolutionised timber construction, enabling the efficient construction of largescale structures with enhanced durability and performance [62].…”
Section: Timber Jointsmentioning
confidence: 99%
“…The results showed that the average tensile strength of bolt connection was 1354.3 N and the average compressive strength was 652.9 N, which indicated that the corner was more easily damaged under pressure than under tension. Zhou et al [61] proposed an energy dissipation joint of bamboo/timber structure (Fig. 9).…”
Section: Study On Performance Of Bolted Jointmentioning
confidence: 99%
“…Further studies showed that common failures in the GLB dowel connections occurred mainly due to shear parallel to the grain and tensile perpendicular to the gain in the connection area (Lathuillière et al 2015;Reynolds et al 2016). To test the effective use of GLB in construction, limited efforts have been placed to investigate the dowel type GLB connections subjected to bending moment (Zhou et al 2018;Leng et al 2020), and the brittle failure parallel to the grain from the connection was observed.…”
Section: Introductionmentioning
confidence: 99%